TEST OF THE EFFECTIVENESS SQUATTING POSITION IN REDUCING THE DURATION OF THE SECOND STAGE OF LABOR - Farida, Siti; Sulistiyanti, Anik; Fernandes, Angelina da Costa; Xao, Maria Margaretha Xan (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The second stage of labor is a crucial phase that influences maternal and neonatal outcomes. Its duration is an important indicator of whether labor progresses normally or requires intervention. Birthing position plays a role in this process. The squatting position is expected to facilitate cervical dilation and fetal head descent, thus shortening the second stage. This study aimed to determine the effect of squatting on the duration of the second stage of labor. An experimental design was conducted with two groups: 15 mothers delivering in the squatting position and 15 in the lithotomy position. Data on the duration of the second stage were collected through observation and analyzed using the t-test. Results showed a significant difference between groups (p = 0.000 < 0.05). Mothers in the squatting position experienced a shorter second stage compared to those in the lithotomy position. The squatting position was proven to enhance contractions, improve the mechanism of labor, and facilitate optimal opening of the birth canal. It can be considered a safe and effective alternative birthing position to accelerate delivery, provided there is adequate education and professional supervision.